Comparison of the Effects of Inorganic or Amino Acid-Chelated Zinc on Mouse Myoblast Growth in vitro and Growth Performance and Carcass Traits in Growing-Finishing Pigs - Zhang, Lingyu; Guo, Qiuping; Duan, Yehui; Lin, Xue; Ni, Hengjia; Zhou, Chuanshe; Li, Fengna (Frontiers in Nutrition, 2022)
This study aimed to investigate the effects of the supplementation of different zinc sources on mouse myoblast growth in vitro and growth performance and carcass traits in growing-finishing pigs. In the in vitro trial, 25 mM or 75 mM zinc sulfate (ZnSO4), methionine-chelated zinc (ZnMet), and glycine-chelated zinc (ZnGly) were co-cultured with the myoblast during proliferation and differentiation. The results showed that the amino acid-chelated zinc supplementation, especially ZnMet, enhances the cell proliferation and differentiation in mouse myoblast, and regulated the distribution in S and G2/M phases (P <0.05). Meanwhile, the protein expression levels of the mammalian target of rapamycin (mTOR) pathways were all up-regulated after treatment with 25 μM ZnMet (P < 0.05), which is consistent with the results of enriched Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway in the transcriptome analysis. In the in vivo trial, 27 Duroc × (Landrace × Large White) pigs with an initial average weight of 31.62 ± 0.36 kg were divided into three groups with nine replicates per treatment. The dietary treatment groups were as follows: (1) ZnSO4 group, basal diet +75 mg/kg ZnSO4; (2) ZnMet group, basal diet +75 mg/kg ZnMet and (3) ZnGly group, basal diet +75 mg/ kg ZnGly. The whole trial lasted for 75 days. Increased final body weight and average daily gain, and decreased F/G were noted in the ZnMet group (P < 0.05). Moreover, the ZnMet group had higher carcass weight and loin eye area (P = 0.05). The ZnMet and ZnGly group both had lower serum total protein (P < 0.05), while the ZnMet group had higher serum alkaline phosphatase (P < 0.05). In addition, the addition of ZnMet showed higher concentrations of zinc and iron in muscle, kidney, and serum (P < 0.05), improving the deposition and availability of micronutrients. In conclusion, amino acid-chelated zinc, particularly ZnMet, had the best effect, which could improve growth in vitro and increase growth performance while boosting bioavailability in growing-finishing pigs, ultimately enhancing muscle mass, providing a theoretical basis and guidance for the future use of amino acid-chelated zinc to effectively replenish energy in animal nutrition and production.